Bat Assemblages along an Elevational Gradient in Costa Rica - Pineda Lizano, Willy (2022)
Spatio-temporal patterns of species richness, Hill numbers, captures per species, feeding guilds, sex ratio, and biomass were studied in a Neotropical bat assemblage during 17 continuous months in four bands (low: 50–150, mid-low: 375–500, mid-high: 975–1,050, and high: 1,950–2,050 m a.s.l.) in an elevational gradient in Costa Rica. We found an effect of elevation on species richness. As expected, species richness was high in the low elevations; unexpectedly, however, we noted that species richness was highest in the mid-high band, a diversity pattern that has not been previously recorded in bats. We also found an effect of precipitation periods on species richness; in particular, at mid-high elevations, when precipitation was intermediate and highest, we observed a larger number of species. When analyzing data separately by feeding ensemble, we found an effect of elevation on species richness for three ensembles: animalivorous bats were more diverse at the mid-low band, nectarivorous bats were more diverse in the mid-high and high bands, and frugivorous bats were more diverse in the mid-low and low bands. Species richness of frugivorous bats was also affected by precipitation; when rainfall was intermediate and highest, we noted a higher species richness of this ensemble. There was no effect of elevation on species richness for the insectivorous, omnivorous or hematophagous ensemble, nor on the species capture, sex ratio or biomass. Our results not only provide further evidence of the importance of lowland forests as reservoirs of high species diversity, but also highlight the importance of tropical premontane rainforests for the conservation of bat communities given their high species richness, particularly for the nectarivorous and frugivorous ensembles. This is particularly relevant not only because this ecosystem has been heavily affected by land use changes in the Neotropical region, but also because the predicted future decrease of precipitation at this elevation could potentially affect overall species richness and particularly for certain feeding ensembles. Thus, conservation efforts in this life zone are of critical importance for maintaining functional and ecological diversity of bat communities in elevational gradients.